2019
DOI: 10.1186/s12909-019-1525-y
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of interprofessional learning between medical and pharmacy students in a prescribing skills training workshop: pre-post intervention study

Abstract: Background The success of interprofessional collaboration in healthcare services requires a paradigm shift in the training of future health profession practitioners. This study aimed to develop and validate an instrument to measure Student Acceptance of Interprofessional Learning (SAIL) in Malaysia, and to assess this attribute among medical and pharmacy students using a prescribing skills training workshop. Methods The study consisted of two phases. In Phase 1, a 10-it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
0
12
0
3
Order By: Relevance
“…The research findings and lessons learnt from our experience respond to a gap in existing IPE literature, which, according to a 2016 review of global health care [7], mostly draws on developedworld undergraduate programs and the nursing profession. Further, whilst there have been numerous publications about IPE from Australia [20][21][22][23][24] and Malaysia [25][26][27][28][29], we identified no published investigations of the overlap of professional and geographical systems with regard to perceptions of collaborative care. Further research in this respect is important as the healthcare workforce in many areas is becoming more culturally diverse due, in part, to migration for improved employment opportunities.…”
Section: Introductionmentioning
confidence: 95%
“…The research findings and lessons learnt from our experience respond to a gap in existing IPE literature, which, according to a 2016 review of global health care [7], mostly draws on developedworld undergraduate programs and the nursing profession. Further, whilst there have been numerous publications about IPE from Australia [20][21][22][23][24] and Malaysia [25][26][27][28][29], we identified no published investigations of the overlap of professional and geographical systems with regard to perceptions of collaborative care. Further research in this respect is important as the healthcare workforce in many areas is becoming more culturally diverse due, in part, to migration for improved employment opportunities.…”
Section: Introductionmentioning
confidence: 95%
“…Moreover, there are few universities in Malaysia that conduct IPE either physically or online [28]. The effectiveness of conducting IPE virtually has not been tested and cannot be compared with existing results regarding the physical implementation of IPE in other countries.…”
Section: Effectiveness Of Conducting Interprofessional Educationmentioning
confidence: 99%
“…Organising IPE is challenging in all countries due to the logistical challenges delivering sessions to large numbers of students and competing curricula priorities [83][84][85]. Reports of IPE activities are predominantly from developed countries, with developing countries such as Malaysia incorporating IPE into healthcare education curricula more recently [86][87][88][89]. Brock et al recently reported on the development of an IPE activity for medical and pharmacy students at Monash University, delivered on their Australian and Malaysian campuses [90].…”
Section: Interprofessional Educationmentioning
confidence: 99%